RC-DBSCAN: redundancy controlled DBSCAN algorithm for densely deployed wireless sensor network to prolong the network lifespan. (14th December 2021) - Sharma, Tripti; Mohapatra, Amar Kumar; Tomar, Geetam Singh
In wireless sensor networks, the nodes are spatially distributed and spread over application-specific experimental fields. The primary role of these nodes is to gather the information intended for various fields like sound, temperature, etc. In this proposed algorithm the efforts have been made to raise the network lifespan by decreasing the nodes' energy consumption by considering the critical issues of dense deployment. The network area is divided into a high and low-density region using the DBSCAN algorithm. The division regions by applying DBSCAN helps in sleep management. Sleep management helps in energy optimisation in dense areas and thus aids in prolonged network lifetime and improved stable region. Simulation result yields that the RC-DBSCAN is more energy efficient than the IC-ACO and LEACH in densely deployed network areas in terms of total data packets received by the base station, prolonged network lifespan and improved stability period.